THE FUTURE OF NURSING EDUCATION: THE INTEGRATION OF SIMULATION-BASED LEARNING AND TECHNOLOGY - Catur Budi Susilo; Amin Zaki; Rina Farah (Yayasan Adra Karima Hubbi, 2026)
Rapid technological advancement and increasing complexity in healthcare systems require nursing education to evolve beyond traditional instructional approaches. Simulation-based learning supported by digital technologies has emerged as an innovative educational strategy that allows nursing students to develop clinical competence, critical thinking, and decision-making skills in safe and controlled environments. This study aims to examine the integration of simulation-based learning and technological tools in nursing education and evaluate their influence on students’ learning engagement, clinical confidence, and professional competence development. The research employs a mixed-method approach combining quantitative survey analysis with qualitative observations and interviews. Data were collected from nursing students and instructors participating in simulation-based learning sessions using high-fidelity mannequins and virtual simulation platforms. Statistical analysis was conducted to examine learning outcomes, while thematic analysis was used to interpret participants’ experiences. Findings indicate that simulation-based learning significantly improves students’ clinical confidence, engagement, and critical thinking abilities. High-fidelity simulations enhance clinical skill acquisition, while virtual simulations increase accessibility and flexibility in learning. Integration of simulation-based learning and technology represents a transformative strategy for modernizing nursing education and preparing future nurses for technologically advanced healthcare environments.